Effects of Glyphosate Herbicide on Photosynthetic Pigments and Antioxidant Enzyme Activities in Corn (Zea mays L.) and Wheat (Triticum aestivum L.) Varieties - Karabulut, Fadime; Gülengül, Songül Çanakcı (Niyazi BULUT, 2021)
In this study, it was determined that phytotoxic levels of glyphosate herbicide that will be banned in Europe may be at on wheat and corn plants. Biochemical responses due to the toxic effect of glyphosate at different concentrations were determined in corn (Zea mays L. cv. Ada 523) and wheat (Tritucum aestivum L. cv. Halis) varieties. For wheat and corn varieties, 4 different doses (0, 100, 500 and 1000 ?M) of the herbicide were applied to 1-week-old and 15-day-old plants. Hydroponic medium was used for all applications on plants. According to the results obtained; the toxic effect created by glyphosate increased the destruction of pigment in the leaves and significant decreases were detected. While GST, SOD and CAT activities increased in all concentrations of 1-week-old plants treated with glyphosate, only GST activity decreased at 100 ?M concentration of wheat leaf and corn root. SOD and CAT activities were increased in 15-day-old wheat and corn plants treated with glyphosate. Only SOD activity decreased in the root part of the maize plant. GST activity was increased in the roots and leaves of the maize plant, while it decreased in wheat leaves and roots at a concentration of 100 ?M. As a result, glyphosate was found to be effective at very low concentrations in wheat and corn regardless of age. It was also revealed that 1-week-old corn and wheat crops inhibit more phytotoxic effects than these 15-day-old plants. In other words, young plants were found to be more resistant.
Keywords: Chemical Engineering; Kimya Mühendisliği